Diversity of parasitic helminths associated with lizards in a little studied environment in the Caatinga domain, northeastern Brazil - Cardoso Lacerda, Glória Maria (2026)
This study presents the composition of the helminth community and the parameters of parasitic infection (abundance, prevalence, mean intensity of infection) of five species of lizards collected in an area of Carrasco in the Northeast region of Brazil. Collections were made between May and September 2021 in a carrasco environment located in Chapada do Araripe, Ceará state, Brazil. Specimens were captured using traps and also manually during active searches. The parasites found were collected and infection patterns estimated for each species. A total of 239 parasites were collected from 21 hosts. The community was predominantly composed of nematodes. The lizard Phyllopezus pollicaris (Spix, 1825) had the highest parasitic diversity, and the nematode species S. oxkutzcabiensis Chitwood, 1938 was the most prevalent in the community. Most nematode species were found in the gastrointestinal tract of the hosts. Parasitic members of the Pharyngodonidae family were the most common nematodes found. We found strong similarities in the composition and distribution of endoparasite species in the Carrasco and the adjacent Caatinga environments. The endoparasite community recorded was diverse, and some nematode species were associated with specific host species. The lizards E. bibronii Boulenger, 1885 Boulenger, 1885 and P. pollicaris are recorded here as new hosts for Onchocercidae and P. travassosi Pereira, 1935, respectvely. The data presented here provide new information, expanding knowledge about the composition of the helminthological fauna of lizards occurring in the Caatinga.